Optimalisasi Komunikasi Damai Dalam Menyongsong Pilgubsu 2024 Pada Warga Kelurahan Mangga - Sarah, Eva Margareth; Hia, Niscaya; Siregar, Marupa (JPM: Jurnal Pengabdian Masyarakat, 2025)
The partner of this community service activity is the mango village, medan tuntungan sub-district. The purpose of this assistance activity is to increase knowledge about the procedures for implementing elections through peaceful communication, increase the sense of unity between residents so that the elections to be held can run orderly and smoothly due to the large amount of information or fake news that makes people become anarchist during the election period. the method of implementing social service activities includes using the socialization method. The participants get a positive and interesting impression, which allows them to understand the importance of non-violent communication for the community and participants during the election period. Every participant who took part in the pendampingan activities on peaceful communication did so with great enthusiasm. Based on the results of observations of the implementation of community service activities in the form of peaceful communication pendampingans, it is recommended that developing collaboration with institutions and organizations to develop this program and expand its impact to the people of North Sumatra.